Agri-business for elderly people through the Internet - Kenji Hashimoto (Netcom)
The leaf business of Irodori is an example of a successful enterprise realized by connecting elderly people and local agricultural resources in a peripheral area with an aging population. In the process of developing the business, Irodori has overcome three difficulties with regard to information systems. Firstly, it overcame the distances between the peripheral producing regions and the consumer markets in urban areas. Secondly, it overcame the disadvantageous condition of being based in a mountain village with a low population density, where it is difficult to develop a communications infrastructure. Thirdly, it overcame the difficulty and burden that elderly people felt regarding the use of a personal computer and the Internet. The example of Irodori can be considered as a model case when considering the exploitation of regional resources and strategies for utilizing them through 'informatization'.